Aged smart-care application program for promoting quality of life among older adults in the community: Study protocol of a three-arm randomized controlled trial - Yue Xu; Qiyuan Huang; Shuang Teng; Yulong Wang; Huabei Sun; Mei Li; Junxin Li; Muwei Zhu; Xianping Tang (Digital Health)
Objectives To describe a study protocol for a three-arm randomized controlled trial that will evaluate the effectiveness of an Aged Smart-Care (ASC) application program intervention for community-dwelling older adults in China. Methods This randomized controlled trial with three arms will be conducted at eight community health service centers. Participants will be randomly assigned to one of three groups: the interactive ASC (ASC + I) group, the regular ASC group, or the control group. The ASC + I group will receive management from a multidisciplinary medical team, while the regular ASC group will only utilize the ASC. The primary outcome will be assessed using the Medical Outcomes Study Short Form 36 (SF-36) Health Survey. The secondary outcomes include general self-efficacy, medication adherence, effectiveness of health behavior interventions, BMI, number of outpatient visits, and number of hospitalizations. Data will be collected at baseline, immediately post-intervention, 3 months, 6 months, and 1 year after the intervention. Generalized estimating equations model will be employed for data analysis. Conclusions This study clarifies the development process of the ASC and designs a three-arm randomized controlled trial to examine the efficacy of the ASC for older adults in the community. The results of the study will compare differences in the quality of life of participants in different groups. This will help community healthcare workers to choose appropriate interventions regarding the ASC. Furthermore, this provides scientific guidance for the Integrated Theory of Health Behavior Change theory in the field of mobile health tool development.